Gambaran Pemeriksaan Kadar SGOT dan SGPT pada Penderita Tuberkulosis Paru - Chairini, Siti; Widodo, Widodo (Jaringan Laboratorium Medis, 2020)
Liver disfunction is characterized by increased levels of SGOT and SGPT. The mechanism of liver disfunction by anti-tuberculosis drug (ATD) is not yet clearly known, but several research mention the occurrence of hepatotoxicity which caused by direct effect or through the complex production of drug enzyme which have consequences in cell disfunction as well as membrane disfunction. Hepatotoxicity due to ATD does not occur in each patient, but it could cause liver injury. research objective to find out the description of examination of SGOT and SGPT levels in patients of pulmonary tuberculosis. The research type was descriptive using medical records data and laboratory data of RSUP patients of pulmonary TB in January-March 2020. Research results : the normal SGOT levels in men 6-33 U/L as much as 63,33%, and SGOT > normal 50-66 U/L as much as 2,35%. The normal SGOT levels in women 10-25 U/L as much as 25,88%, and SGOT > normal in women 15-63 U/L as much as 8,24%. The normal SGPT levels in men 3-43 U/L as much as 62,35%, and SGPT > normal 55-65 U/L as much as 3,53%. The normal SGPT levels in women 7-29 U/L as much as 34,12%. Hepatotoxicity based on SGOT levels as many as 9 people (10,59%), namely 2 men (elderly and old man) and 7 women (adolescent, adult, and elderly). Hepatotoxicity based on SGPT levels as many as 3 people (3,53%) in elderly and old man.